Local cytokine treatment of HPV16-associated tumours results in inhibition of their lung metastases - Mikysková, R; Bubenik, J; Mendoza, L; Vonka, V; Smahel, M; Símová, J; Jandlová, T (Clinical & experimental metastasis, 2000)
Experiments were designed to examine whether local cytokine therapy of subcutaneous (s.c.) tumours results in inhibition of their lung metastases. Moderately immunogenic, major histocompatibility complex (MHC) class I and II negative. B7 negative, metastasizing murine carcinoma MK16 transplantable in syngeneic mice was obtained by co-transfection of human papilloma virus type 16 (HPV 16) E6/E7 and activated H-ras oncogene plasmid DNA into C57BL/6 kidney cells. After s.c. transplantation of the malignantly converted MK16 cells, the majority of the transplanted mice developed lung metastases; the number and size of the lung metastases increased with the increasing size of the s.c. tumour. Therapy of 5-day MK16 tumours by peritumoral administration of recombinant interleukin-2 (IL-2) and recombinant interleukin-12 (IL-12) inhibited growth of the s.c. MK16 tumour transplants and reduced the number of MK16 lung metastases. To investigate the antimetastatic effect of IL-2 and IL- 12 in a clinically more relevant setting, surgical minimal residual tumour disease was utilized. Subcutaneously growing MK16 carcinomas, 8-12 mm in diameter, were removed on day 30 and the operated mice were injected with IL-2 or IL- 12 on days 35-39 and 42-46 at the site of the operation. Treatment with IL-2 significantly reduced the percentage of MK16 tumour recurrences as well as the number of lung metastases, whereas the effect of IL- 12 was substantially weaker and statistically insignificant.
Keywords: Tumor Virus Infections; buněčné dělení; transplantace nádorů; B7-2 Antigen; Histocompatibility Antigens; interleukin-2; antigeny CD80; Antineoplastic Agents; Lung Neoplasms; Mice; zvířata; infekce papilomavirem; interleukin-12; protinádorové látky; membránové glykoproteiny; CD antigeny; Papillomavirus Infections; Interleukin-12; nádory plic; Antigens, CD; infekce onkogenními viry; karcinom; antigeny CD86; myši; Membrane Glycoproteins; ženské pohlaví; transformované buněčné linie; Animals; B7-1 Antigen; Mice, Inbred C57BL; Interleukin-2; histokompatibilní antigeny; Carcinoma; Cell Line, Transformed; Cell Division; Neoplasm Transplantation; myši inbrední C57BL; Female